EFEKTIVITAS INJEKSI INTRALESI BEBERAPA JENIS OBAT PADA TERAPI ORAL LICHEN PLANUS : TINJAUAN SISTEMATIK - Adi Ahmad Yusuf; Nanan Nuraeny (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Oral lichen planus (OLP) is a chronic inflammatory disease with unknown etiology. The immune system plays a role in this disease, a sub-epithelial band infiltration is dominated by T lymphocytes and macrophages is visible histopathologically. Stress, genetics, diet, drugs, dental plaque, systemic disease, and poor oral hygiene are thought to trigger OLP. Treatment of this disease usually uses topical corticosteroids in the form of an ointment, mouthwash, spray or paste or systemic corticosteroids, but in some patient there are unwanted side effects of systemic and topical corticosteroids such as moon face and hirsutism. Intralesional corticosteroid injections are topical therapy and can be used to reduce these side effects. The purpose of this systematic review is to provide information on the effectiveness and types of drugs used in the treatment of OLP by intralesional injection. Methods: A literature search was conducted using electronic databases including PubMed and Google Scholar. Only articles in English and Indonesian are included, with keywords intralesional injection, oral lichen planus, and therapy. Cohort study, randomized controlled trial, and research between 2010 and 2020. Results: A total of 1,179 articles were obtained according to the keywords, but after eliminating duplication and screening based on abstracts, 8 articles were obtained, with 4 types of drugs being used for intralesional injection therapy in OLP, namely Triamcinolone acetonide, Bacillus Calmette Guerin-Polysaccharide Nucleic Acid (BCG-PSN), bethametasone and bevacizumab. Conclusion: Intralesional injection with Triamcinolone acetonide, betamethasone, BCG-PSN, and bevacizumab drugs is effective in treating oral lichen planus.